An alpha‐defensin gene single nucleotide polymorphism modulates the gut microbiota and may alter the risk of acute graft‐versus‐host disease. (21st February 2020) - Rashidi, Armin; Herman, Adam; Gomes, Antonio L. C.; Peled, Jonathan U.; Jenq, Robert R.; Brereton, Daniel G.; Staley, Christopher; Blazar, Bruce R.; Weisdorf, Daniel J.
Summary: We previously reported a protective association between single nucleotide polymorphisms (SNPs; rs4415345G and rs4610776A alleles) of Paneth cell α‐defensin‐5 against acute graft‐ versus ‐host disease (aGVHD). Because dysbiosis has been associated with aGVHD, we hypothesized that these SNPs may have a gut microbiota signature. In Lasso regression analysis of 248 healthy individuals, rs4415345G was associated with a higher abundance of Odoribacter splanchnicus, an anaerobic butyrogenic commensal. In multivariable analysis of data from 613 allogeneic haematopoietic cell transplant recipients, peri‐engraftment presence of O. splanchnicus was associated with ~50% lower risk for grade II–IV aGVHD (hazard ratio 0·53, 95% confidence interval 0·28–1·00, P  = 0·05). O. splanchnicus may protect rs4415345G individuals against aGVHD.